Calibration and comparison of VIV wake oscillator models for low mass ratio structures. (July 2018) - Kurushina, Victoria; Pavlovskaia, Ekaterina; Postnikov, Andrey; Wiercigroch, Marian
Highlights: Vortex-induced vibrations of elastically-supported cylinders are considered. Wake oscillator models with different types of nonlinear damping are studied. Published experimental data for low mass ratio are used for models calibration. The suitable damping for in-line and cross-flow wake oscillators are identified. Graphical abstract: Abstract: In this work, Vortex-Induced Vibration (VIV) of a rigid cylinder on elastic supports is reviewed and modelled. We consider a cylinder moving both cross-flow and in-line subjected to fluid forces calculated as proposed in [1]. A suite of wake oscillator models is investigated with different types of nonlinear damping in the fluid equation, where sets of model coefficients are optimized for each variation of the nonlinear damping using the constrained nonlinear minimization. The calibration is based on the experimental data presented by Stappenbelt and Lalji [2]. The largest displacement amplitude is used as the main calibration criterion to determine empirical coefficients of the fluid equations. The frequency difference between the beginning of resonance evaluated from the base model[1] and the experimental data[2] is used as an additional coefficient for calibration. The developed models are cross-checked using four sources of published experimental data [3, 4, 5, 6]. This allows to identify the most suitable wake oscillator models which are applicable for a wide variety of experimental data. The main outcome of this research is a library of calibrated models describing fluid-structure interactions at low mass ratio. Specifically, it was shown that the Rayleigh damping is the most suitable for cross-flow equation, whereas the Van der Pol damping is preferable for in-line equation for these low mass ratio cases.